If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 20ab = 30ab + -50 Reorder the terms: 20ab + 10x = 30ab + -50 Reorder the terms: 20ab + 10x = -50 + 30ab Solving 20ab + 10x = -50 + 30ab Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-30ab' to each side of the equation. 20ab + -30ab + 10x = -50 + 30ab + -30ab Combine like terms: 20ab + -30ab = -10ab -10ab + 10x = -50 + 30ab + -30ab Combine like terms: 30ab + -30ab = 0 -10ab + 10x = -50 + 0 -10ab + 10x = -50 Add '-10x' to each side of the equation. -10ab + 10x + -10x = -50 + -10x Combine like terms: 10x + -10x = 0 -10ab + 0 = -50 + -10x -10ab = -50 + -10x Divide each side by '-10b'. a = 5b-1 + b-1x Simplifying a = 5b-1 + b-1x
| (8x+2)-(2x-8)= | | -7=-7x-7(-3-23) | | -2.5+x=-16 | | -5x+10-2x=60 | | 12x^-2/2x^-4 | | 5j-3=12 | | 3(2k-9)-2(k+5)= | | -5+10-2x=-60 | | 7(7x+5)=35+x | | (-5y^3x^2)(-6y^3x^3)(x^2)^-4/40x^3y^2(y^3)^2(x^3)^-2 | | 3-x/3=-7+16 | | 6x-3=4x-7 | | 23-5x=-5x-(1-8x) | | 5y-7x=6 | | -r=7 | | (10x^6+8x^4)/(2x^2)=14x^4 | | 23-5x=-5-(1-8x) | | y-19=-21 | | 6(4x-8)=2(9x+10) | | f(x+2)=7x+20 | | B/8=64 | | 5(x-4)+10=3+2(x-4) | | -5/9-2/3 | | 4.5+x=10 | | 3x*9+(24/8-15) | | 4(5n+3)=7n-27 | | 4y/3+y/15 | | -10/2-i | | 4b-8-b=10b-36 | | 0=t^2-6t-27 | | 3+8y=3y-12 | | -9y=-29 |